2014
DOI: 10.1123/pes.2013-0102
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Impact Force, Neck Strength, and Neurocognitive Performance in Soccer Heading in Adolescent Females

Abstract: Head impacts are common in contact sports, but only recently has there been a rising awareness of the effects of subconcussive impacts in adolescent athletes. A better understanding of how to attenuate head impacts is needed and therefore, this study investigated the relationship between neck strength, impact, and neurocognitive function in an acute bout of soccer heading in a sample of female high school varsity soccer players. Seventeen participants completed the ImPACT neurocognitive test and had their isom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
79
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(87 citation statements)
references
References 29 publications
(38 reference statements)
3
79
1
1
Order By: Relevance
“…Effect size for age was not significant. Seventeen studies sought to determine the impact of football heading on neurocognitive performance, including attention/concentration (k=11), impulse control (k=2), reaction time (k=3), processing speed (k=10), verbal memory (k=16) and visual memory (k=11) 8 13–16 28 33 34 36 37 42–47 49 50. Generally, the effect sizes were small, with the largest effect supported for reaction time (g=0.28).…”
Section: Resultsmentioning
confidence: 99%
“…Effect size for age was not significant. Seventeen studies sought to determine the impact of football heading on neurocognitive performance, including attention/concentration (k=11), impulse control (k=2), reaction time (k=3), processing speed (k=10), verbal memory (k=16) and visual memory (k=11) 8 13–16 28 33 34 36 37 42–47 49 50. Generally, the effect sizes were small, with the largest effect supported for reaction time (g=0.28).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, this method is not suitable for quantifying heading in amateur players who are not typically tracked by coaches or athletic trainers. Wearable accelerometers are attractive because they offer the promise of quantitative characterization of head impacts (Gutierrez, Conte, & Lightbourne, 2014; McCuen et al, 2015) and because they are becoming smaller and thus less cumbersome to wear during athletics, as well as more affordable (Ciuti, Ricotti, Menciassi, & Dario, 2015). However, the reliability and validity of these devices has been shown to be low in soccer (Press & Rowson, 2016), and they still require confirmation with direct observation or analysis of video to determine impact types (Hanlon & Bir, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…14 In addition, neck strength was negatively correlated with header acceleration in high school female soccer athletes. 15 Less overall neck strength has been significantly correlated with concussion rates in basketball, lacrosse, and soccer. 16 Accordingly, researchers 6,13,16 have indicated that neck-strengthening exercises might be a preventive tool and emphasized the need for further, more definitive research.…”
mentioning
confidence: 99%